2010
DOI: 10.4149/neo_2010_04_287
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor IIH – the protein complex with multiple functions

Abstract: Transcription factor IIH (TFIIH) is eukaryotic multi protein complex identified in early 90's. Subsequent years have shown exceptional conservation of its structure from yeast to human. Although initially considered to be exclusively a basal transcription factor responsible for initiation of transcription and transition from initiation to elongation, TFIIH is also important in nucleotide excision repair for opening DNA at the site of a lesion and for recruitment of additional repair factors. Recently it was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…TFIIH is also a component of the RNA polymerases I–III holoenzymes where it is crucial for transcription initiation and DNA unwinding during the early elongation step. Due to its complex dynamic structure and multifunctionality TFIIH is able to coordinate transcription and DNA repair, and may also relate these processes to the cell cycle control ( Mydlikova et al, 2010 ). The recruitment of TFIIH during NER allows opening of the DNA duplex, which is performed by its key helicase subunits XPB and XPD, each of them bound to a different DNA strand.…”
Section: Dna Repair Pathways In Model and Crop Plants – Nature And Efmentioning
confidence: 99%
“…TFIIH is also a component of the RNA polymerases I–III holoenzymes where it is crucial for transcription initiation and DNA unwinding during the early elongation step. Due to its complex dynamic structure and multifunctionality TFIIH is able to coordinate transcription and DNA repair, and may also relate these processes to the cell cycle control ( Mydlikova et al, 2010 ). The recruitment of TFIIH during NER allows opening of the DNA duplex, which is performed by its key helicase subunits XPB and XPD, each of them bound to a different DNA strand.…”
Section: Dna Repair Pathways In Model and Crop Plants – Nature And Efmentioning
confidence: 99%
“…Indeed, Tfb3 is needed for efficient neddylation of Cul3 and for neddylation and ubiquitylation of Rtt101, two yeast cullins regulating DNA-associated processes. Tfb3 is an essential subunit of the TFIIH complex, which mediates transcription initiation and is also involved in nucleotide excision repair (NER) (Mydlikova et al, 2010). Because we have not found other mutations in TFIIH subunits that affect Rtt101 modification, it is unlikely that activation of Rtt101 and Cul3 neddylation is linked to TFIIH function in transcription initiation or NER.…”
Section: Discussionmentioning
confidence: 99%
“…Tfb3 is part of TFIIH, a well characterized complex involved in transcription initiation and nucleotide excision repair (NER) (Mydlikova et al, 2010). To determine whether these functions of TFIIH are involved in Rtt101 regulation, we examined Rtt101 modification in various TFIIH mutants with impaired transcription or NER activities.…”
Section: Tfb3 Probably Regulates the Conjugation Step Of Cullin Neddymentioning
confidence: 99%
“…Finally, it has been recently shown that additional factors can be required to ensure the efficient neddylation of specific cullins. TFB3, an essential subunit of the TFIIH complex, which mediates transcription initiation and is also involved in nucleotide excision repair (NER) [29], is needed for efficient neddylation of CUL3 and for neddylation and ubiquitylation of Rtt101, two yeast cullins regulating DNA-associated processes [30].…”
Section: (Senp8mentioning
confidence: 99%